Combined intravitreal bevacizumab and triamcinolone in exudative age-related macular degeneration - Jonas, Jost B.; Libondi, Teodosio; Golubkina, Lidia; Spandau, Ulrich; Schlichtenbrede, Frank; Rensch, Florian (Acta ophthalmologica, 2010)
Acta Ophthalmol. 2010: 88: 630-634 Abstract. Purpose: We report on the combined application of intravitreal bevacizumab and triamcinolone acetonide for treatment of exudative age-related macular degeneration (AMD). Methods: The clinical interventional case-series study included 16 patients (16 eyes) with exudative AMD who had previously received 3.5 ± 1.8 mono-injections of bevacizumab (1.5 mg) without significant improvement in visual acuity (VA) or reduction in macular exudation. All patients underwent a combined intravitreal injection of bevacizumab (1.5 mg) and triamcinolone acetonide (about 20 mg). Main outcome measures were VA and macular thickness as determined by optical coherence tomography. All patients were re-examined at 2-3 months after the intervention. Results: Visual acuity improved significantly (p = 0.03) from 0.80 ± 0.40 logMAR prior to the combined injection to 0.65 ± 0.42 logMAR at 3 months after the injection. An improvement of ≥ 1 Snellen line was found in eight subjects, an increase of ≥ 2 lines in five subjects, and an improvement of ≥ 3 lines in two subjects. One patient lost 1 line and one patient lost 3 lines. Central retinal thickness decreased significantly from 272 ± 62 μm to 220 ± 47 μm (p = 0.03). At the 6-month follow-up examination, central retinal thickness had increased again to 319 ± 142 μm, which was not significantly (p = 0.30) different from baseline measurements. Conclusions: The combined intravitreal application of bevacizumab and triamcinolone may temporarily be helpful in the treatment of exudative AMD if previous intravitreal bevacizumab mono-injections have failed to improve vision and reduce macular oedema.
First published: 27 August 2010
Gesehen am 28.08.2023